Human case of Onchocerca dewittei japonica infection in Fukushima, Northeastern Honshu, Japan. (October 2019) - Fukuda, Masako; Uni, Shigehiko; Igari, Takahiro; Utsumi, Yasufumi; Otsuka, Yasushi; Nakatani, Jun; Uga, Shoji; Hara, Tatsuru; Hasegawa, Hideo; Takaoka, Hiroyuki
Abstract: A 73-year-old man living in Kawamata-machi, Fukushima Prefecture, Northeastern Honshu, Japan, visited a hospital with complaints of a subcutaneous swelling that had developed on the back of his left hand. The nodule was surgically removed from the vagina fibrosa tendinis of his left forefinger. Based on the histopathological characteristics, the causative agent of this nodule was identified as a female Onchocerca dewittei japonica (Spirurida: Onchocercidae). The species identification was confirmed by cox 1 gene sequencing of the worm tissues from paraffin-embedded sections of the nodule. Although 11 cases of zoonotic onchocercosis have previously been recorded in Kyushu and Western Honshu, Japan, the present findings represent the first human case of infection with O . dewittei japonica in Northeastern Honshu, Japan. Graphical abstract: Unlabelled Image Highlights: A subcutaneous nodule was surgically removed from a patient in Fukushima, Japan. Histopathological analysis identified the causative agent as O . dewittei japonica . Species identification was confirmed by partial sequencing of the cox 1 gene. This is the first case of human zoonotic onchocercosis in Northeastern Honshu.